PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR BAGI PETANI DI KEBUN BUAH KOTA TOBELO, HALMAHERA UTARA - Kastanja, Ariance Yeane; Patty, Zeth (HIRONO : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to train farmers in the process of making liquid organic fertilizer, due to the lack of knowledge and skills of farmers in the orchards about liquid organic fertilizer, the benefits and how to make it. The methods used are counseling, asking questions and training to directly make liquid organic fertilizer (POC). The results showed that there was an increase in knowledge and skills of farmers. Some indicators have experienced a very high increase of 85% - 90%, for example the composition of POC material, the stages of manufacture and manufacture, while other indicators such as knowledge about POC, EM4 introduction, how to make and application of liquid organic fertilizer (POC) which has increased by up to 70%.